Diagnosing reliability problems in Socio‐technical Systems: A Visualisation approach - Gregoriades, Andreas; Sutcliffe, Alistair G. (My University, 2003)
This paper presents a visualisation approach of socio‐technical system design evaluation based on human reliability. Bayesian Belief networks are used to assess human error and system failure (Sutcliffe et al. 1999) based on a variety of high‐level operational scenarios. The System Reliability Analyser tool automates the process by iteratively manipulating the BBN model, presenting the analyst with a three‐level visualisation of the results to diagnose the locus of reliability problems. A case study is presented on the evaluation of two alternative designs of the command and control room of an offshore patrol vessel.